جماليات السرد في شعر حسين مردان - جبار طه عبد القادر (Al-Adab Journal, 2018)
The research point out that poet of Hussein Mardan achieved its self-genera through the overall elements of poetry, weight, rhyme, rhythm procedure, the poetic image, irony, and the language that transcends the language itself, and if there are common elements in the poetry, the poem of Hussein Mardan had its own specificity of blowing up power of optical modulation, by investing in the form of vertical poem the poem trochee and merged together and take advantage from the aesthetic elements each, in the weight there was a deviation of basic trochee for seas of poetry and one of the elements of diversification of rhythm and take it out of usual stereotyped as in the sea shun jumper in tfilth and turned with Hussein Mardan to the slow- rhythm Bahr, in the structure of poetic narrative Hussein Mardan has been able to employ some techniques narrative poetry in enriching the text through a dialectical relationship between the two extremes and enrich the poetic text and move to higher levels in language, pictures and paradoxically.